Humic acid batteries derived from vermicomposts at different C/N ratios - Shamsuddin, R.M. (Institute of Physics Publishing, 2017)
Humic acid is a known fertilizer derived from decomposed organic matters. Organic wastes are normally landfilled for disposal which had contributed negatively to the environment. From waste-to-wealth perspective, such wastes are potential precursors for compost fertilizers. When worms are added into a composting process, the process is termed as vermicomposting. In this work, humic acid from vermicompost derived from campus green wastes was developed into a battery. This adds value proposition to compost instead of being traditionally used solely as soil improver. This research work aimed to study the correlation between electrical potential generated by humic acid at different Carbon to Nitrogen (C/N) ratios of vermicompost at 20, 25, 30 and 35. The temperature and pH profiles of composting revealed that the compost was ready after 55 days. The humic acid was extracted from compost via alkaline extraction followed by precipitation in a strong acid. The extracted humic acid together with other additives were packed into a compartment and termed as vermibattery. Another set of battery running only on the additives was also prepared as a control. The net voltage produced by a single vermibattery cell with Zn and PbO electrodes was in the range of 0.31 to 0.44 V with compost at C/N ratio of 30 gave the highest voltage. The battery can be connected in series to increase the voltage generation. Quality assessment on the compost revealed that the final carbon content is between 16 to 23 wt, nitrogen content of 0.4 to 0.5 wt, humic acid yield of 0.7 to 1.5 wt and final compost mass reduction of 10 to 35 wt. Composting campus green wastes carries multi-fold benefits of reducing labour requirement, generating fertilizer for campus greenery and green battery construction. © Published under licence by IOP Publishing Ltd.